Evaluation of Radiation dosimetry of (99m)Tc-HYNIC-PSMA and imaging in prostate cancer - Zhang, Jianping (Sci Rep, 2020)
This study aims to evaluate the radiation dosimetry of a new technetium-99m‒labelled small-molecule inhibitor of prostate-specific membrane antigen (HYNIC-Glu-Urea-A, (99m)Tc-HYNIC-PSMA) and its feasibility as a tumor-imaging agent in prostate cancer (PCa) patients. A total of 15 PCa patients were enrolled in this study. For the dosimetry study, 5 PCa patients received whole-body planar scans at 0.5 h, 1 h, 2 h, 4 h and 8 h after (99m)Tc-HYNIC-PSMA injection. The Dosimetry Toolkit (GE, Milwaukee) was used to process the data and segment the organs in the SPECT/CT images, which were then projected onto planar images. The organ-specific absorbed doses, total-body absorbed doses and (99m)Tc-HYNIC-PSMA effective doses of patients were calculated using OLINDA/EXM 1.1 software. Whole-body SPECT/CT images were also acquired from additional 10 prostate patients to investigate the feasibility of (99m)Tc-HYNIC-PSMA for imaging tumors by calculating the ratio of tumor-to-background tracer uptake at 2 h after 740 MBq administration. The total-body absorbed dose was 1.54E-03 ± 2.43E-04 mGy/MBq, and the effective dose was 3.72E-03 ± 4.5E-04 mSv/MBq. Compared to published studies of other similar PSMA tracers and (99m)Tc-targeted conventional tracers, the absorbed doses of (99m)Tc-HYNIC-PSMA in all organs showed that it could be used safely in the human body. In addition, (99m)Tc-HYNIC-PSMA showed high tracer uptake (with a tumor-to-background ratio of 9.42 ± 2.62) in the malignant lesions of PCa patients, making it a promising radiopharmaceutical imaging method for site-specific management of PCa.